Application of terrestrial laser scanning for 3D building modelling - Wong, Yen Nee, 1987-; Zulkepli Majid; Fakulti Geoinformasi dan Harta Tanah (2011)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2011